Legal Magazine “Ius et Lex” as a Space for Debate on the Categories of Ius and Lex. Part I - Nowak, Andrzej (Sensus Historiae, 2022)
The article analyzes the interrelationship between ius and lex - categories already formed in antiquity. The opposition and complementarity occurring between these concepts was indicated, on the one hand, by giving historical and literary (ancient and modern) cases of antinomy between natural law and the state law; and, on the other hand, through the so-called “hard cases” occurring in law today, whose presence is generated by an increasingly complex reality.